Resolving the spin splitting in the conduction band of monolayer MoS2. Issue 1 (December 2017) - Marinov, Kolyo; Avsar, Ahmet; Watanabe, Kenji; Taniguchi, Takashi; Kis, Andras
Abstract Time-reversal symmetry and broken spin degeneracy enable the exploration of spin and valley quantum degrees of freedom in monolayer transition-metal dichalcogenides. While the strength of the large spin splitting in the valance band of these materials is now well-known, probing the 10–100 times smaller splitting in the conduction band poses significant challenges. Since it is easier to achieve n-type conduction in most of them, resolving the energy levels in the conduction band is crucial for the prospect of developing new spintronic and valleytronic devices. Here, we study quantum transport in high mobility monolayer MoS2 devices where we observe well-developed quantized conductance in multiples ofe 2 /h in zero magnetic field. We extract a sub-band spacing energy of 0.8 meV. The application of a magnetic field gradually increases the interband spacing due to the valley-Zeeman effect. Here, we extract ag -factor of ~2.16 in the conduction band of monolayer MoS2 . In monolayer transition-metal dichalcogenides, lack of inversion symmetry results in spin-split valence and conduction bands, but the small conduction band splitting is hard to probe experimentally. Here, the authors extract a sub-band spacing energy of 0.8 meV in the conduction band of monolayer MoS2 via quantum transport measurements.